A "masked" source for the phosphaalkene MesP=CH2: Trapping, rearrangement, and oligomerization. Issue 5 (3rd January 2019) - Chen, Leixing; Wang, Shuai; Werz, Patrick; Han, Zeyu; Gates, Derek P.
Abstract: We report the attempted synthesis of a "masked" phosphaalkene by treating MgA·3THF (A = anthracenide) with MesPCl(CH2 Cl). Although the desired "masked" phosphaalkene could not be isolated, indirect evidence for its formation was obtained. The product of trapping MesP=CH2 with 1, 3‐cyclohexadiene was detected. In addition, the oxide MesPO(Me)A was isolated and crystallographically characterized from the MgA·3THF and MesPCl(CH2 Cl) experiment described above. Finally, the attempted isolation of "masked" phoshaalkene afforded P‐containing oligomers with a trimodal molecular weight distribution [ M n  = 640, 1.7 × 10 3 and 7.4 × 10 3  Da].